Comprehensive Identification and Alternative Splicing of Microexons in Drosophila - Pang, Ting-Lin; Ding, Zhan; Liang, Shao-Bo; Li, Liang; Zhang, Bei; Zhang, Yu; Fan, Yu-Jie; Xu, Yong-Zhen (Frontiers in Genetics, 2021)
Interrupted exons in the pre-mRNA transcripts are ligated together through RNA splicing, which plays a critical role in the regulation of gene expression. Exons with a length ≤ 30 nt are defined as microexons that are unique in identification. However, microexons, especially those shorter than 8 nt, have not been well studied in many organisms due to difficulties in mapping short segments from sequencing reads. Here, we analyzed mRNA-seq data from a variety of Drosophila samples with a newly developed bioinformatic tool, ce-TopHat. In addition to the Flybase annotated, 465 new microexons were identified. Differentially alternatively spliced (AS) microexons were investigated between the Drosophila tissues (head, body, and gonad) and genders. Most of the AS microexons were found in the head and two AS microexons were identified in the sex-determination pathway gene fruitless.